Motivation, international posture, and willingness to communicate as predictors of L2 communication in online contexts - Balouchi, Shima; Abd. Samad, Arshad; Ab Jalil, Habibah; Noordin, Nooreen (Inderscience Enterprises, 2021)
A considerable number of studies have emphasised the importance of affective variables in predicting students' second/foreign language (L2) communicative performance. However, the impact of these variables on the L2 frequency of communication (L2 FC) in online contexts is not adequately discussed. This study examines the relations between affective variables [L2 motivation, international posture, and willingness to communicate in a second language (L2 WTC)] and L2 FC in online contexts. This paper also attempts to investigate L2 FC as two separate entities, one for study-related activities and another for leisure-related activities. Data were collected from 245 Malaysian undergraduates and graduate L2 students and analysed using partial least squares structural equation modelling. This study's findings demonstrate the theoretical validity and empirical applicability of Gardner's (1985) socio-educational model and MacIntyre and Charos's (1996) WTC model to the context of online English learning. The obtained results verify the significant roles of affective variables like L2 WTC, motivation, and international posture on learners' L2 communication behaviour in online contexts. It also yields new perspectives on learners' L2 FC in online contexts by pointing that L2 motivation is a significant predictor of L2 FC for study-related activities, while international posture is a significant predictor for leisure-related activities.